4CPS-110 Impact of patients’ conditions on the effectiveness and safety of erlotinib in pancreatic cancer - García, I Muñoz (Eur J Hosp Pharm, 2018)
BACKGROUND: In post-PA studies in the use of erlotoinib, it was observed that the favourable clinical situation benefited the response to treatment. PURPOSE: To compare the effectiveness and safety of erlotinib, according to the Eastern Cooperative Oncology Group (ECOG), in pancreatic cancer. MATERIAL AND METHODS: Retrospective observational study with pancreatic cancer patients treated with erlotinib, in a third-level care hospital from January 2009 to March 2017. A database was developed with demographic, clinical (Selene(®)) and pharmacotherapeutic data (Savac(®)). The data were analysed with SPSS(®) (version23). The level of statistical significance was p≤0.05. RESULTS: We obtained 34 patients, excluding one patient due to insufficiente clinical data. The remaining 33 patients: 57.58% males with a median age of 60.8 years (IQR :54–67). Eighteen patients (54.55%) were smokers. In 28 patients (84.85%), the disease was metastatic and and in five, locally advanced. Erlotinib was used in 15 patients such as the first line (with gemcitabine in 14 of them). Erlotinib in the second line was used in 11 (nine with gemcitabine and one with capecitabine) and seven in the third line (six with gemcitabine). The median progression-free survival (PFS) of the 33 patients was 2.4 months (RI: 1.57–5) and the median overall survival (OS) was 6 months (RI: 2.17–12.17). Subgroup analysis according to ECOG at the start of treatment: characteristics were: a) ECOG <2 (n=17) (ECOG 0 (n=4; 12.12%) and ECOG 1 (n=13; 39.39%)). 58.82% were males with a median age of 59 years (RI: 50–66). Eleven of these patients were smokers and 14 had metastatic disease. Erlotinib was used in the first line in 12 (70.59%) patients, two patients in the second line and 3 in the third line. b) ECOG ≥2 (n=6) (ECOG 2 (n=13; 39.39%) and ECOG 3 (n=3; 9.09%)). 56.25% males with a median age of 61 years (RI: 57–68.25). Seven patientswere smokers and 14 had metastatic disease. Erlotinib was used in the first line in three patients, in 9 in the third line second line and four in the third line. The median PFS of subgruop ECOG <2 was 4.1 months (RI: 1.83–7) versus subgruop ECOG ≥2 with 1.93 months (RI: 1–2.91) (p=0.116). Median OS was 11.67 months (RI: 6–20.17) versus 3.45 months (RI:1.47–6. 02) (p=0.049), respectively. Two patients with ECOG <2 discontinued erlotinib for cutaneous toxicity and renal failure, respectively. The remaining patients discontinued treatment due to disease progression and/or death. CONCLUSION: Patients’ conditions before starting treatment is a determining factor in OS results, however it is not a determinant for PFS. The toxicity was frequent with ECOG <2 but we have not studied the dose influence. Pharmacists must participate in the development of guidelines where patients who will benefit most were selected for treatment with erlotinib. REFERENCES AND/OR ACKNOWLEDGEMENTS: PA. 3 study No conflict of interest